Response to agomelatine treatment is independent of smoking status and dosage: results from the AGOPSYCH study - Englisch, Susanne Angelika; Becker, Anna; Meyer-Lindenberg, Andreas; Zink, Mathias (Pharmacopsychiatry, 2018)
Introduction Cigarette smoking influences response to antidepressant treatment. It accelerates the metabolism of several cytochrome P450 (CYP) subtypes, including CYP1A2, and therefore bears the risk of pharmacokinetic interactions with psychotropic drugs using that pathway. Agomelatine is a substrate of CYP1A2; the association between nicotine use and agomelatine dosage, however, has never been studied before. Methods Smoking habits were correlated with agomelatine doses and treatment outcomes in a sample of 27 patients with lifetime diagnoses within the schizophrenia spectrum who received agomelatine treatment in addition to their stable antipsychotic treatment regimen because of depressive symptoms. Results No interactions were found between smoking status and agomelatine dosage, and treatment outcomes did not differ between smokers and nonsmokers. Discussion Agomelatine efficacy appears to be independent of dosage and smoking status, pointing toward mechanisms beyond mere dose-response relationships. Further research will be necessary to validate these findings.